Right ventricular and atrial functions in systemic sclerosis patients without pulmonary hypertension Speckle-tracking echocardiographic study - SÜNBÜL, MURAT; TİGEN, MUSTAFA KÜRŞAT; DİRESKENELİ, RAFİ HANER (URBAN & VOGEL, 2015)
Background. Systemic sclerosis (SSc) is a systemic connective tissue disease and cardiac involvement is one of the most important causes of death. Right ventricular (RV) systolic dysfunction is a poor prognostic finding in SSc patients. Assessment of RV function has some difficulties because of its crescent shape and extensive trabeculations. Two-dimensional (2D) speckle-tracking echocardiography (STE) is an angle-independent quantitative technique to evaluate myocardial function. The aim of this study was to assess the RV and right atrial (RA) functions of SSc patients without pulmonary hypertension by using 2D STE. Patients and methods. A total of 40 patients with SSc (mean age 48.5 +/- 11.4 years, 28 female) and 40 healthy volunteers (mean age 45.9 +/- 7.6 years, 21 female) were included in the study. All subjects underwent transthoracic echocardiography for evaluation of RV and RA functions with 2D STE. Results. Although left ventricular systolic and diastolic functions, systolic pulmonary artery pressure (PAP), and RA measurements were similar in both groups, tricuspid annular plane systolic excursion (TAPSE) and maximum systolic myocardial velocity (S') were decreased in SSc patients. The RV free wall global longitudinal strain (GLS) of SSc patients was lower than the controls (-18.5 +/- 4.9% vs. -21.8 +/- 2.4%, p< 0.001) and the RA reservoir and conduit functions were also decreased in SSc patients compared with controls (34.4 +/- 9.9% vs. 39.7 +/- 11.2%, p= 0.027 and 15.0 +/- 5.7% vs. 18.7 +/- 6.4%, p= 0.009, respectively). Disease duration was inversely correlated with RVGLS and TAPSE (r: -0.416, p= 0.018 and r: -0.383, p= 0.031, respectively). Conclusion. The use of 2D STE can be helpful in the detection of impairment in RV and RA functions in SSc patients with normal PAP.
Keywords: Systemic sclerosis; Speckle-tracking echocardiography; Strain; Right ventricle; Right atrium; RIGHT HEART FUNCTION; EXERCISE CAPACITY; SYSTOLIC FUNCTION; DOPPLER TISSUE; STRAIN-RATE; DYSFUNCTION; SCLERODERMA; ASSOCIATION; MANIFESTATIONS; IDENTIFICATION